2012
DOI: 10.17221/218/2011-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Czech apple cultivars inferred from microsatellite markers analysis

Abstract: Patzak J., Paprštein F., Henychová A., Sedlák J., 2012. Genetic diversity of Czech apple cultivars inferred from microsatellite markers analysis. Hort. Sci. (Prague), 39: 149-157.Genetic diversity and genetic relationships of Czech apple cultivars were evaluated. Trees of 33 Czech apple cultivars and 97 reference foreign cultivars were analysed using the set of 10 SSR (simple sequence repeat) primer pairs. The total of 89 polymorphic alleles were amplified, while the number of alleles per locus ranged from 4 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Oraguzie et al [ 18 ] reported that clustering did not reflect the pedigree or provenance within the genotypes. No clear patterns of clustering were identified in studies by Gaurino et al [ 20 ] or Garkava-Gustavsson et al [ 21 ] whilst clustering was reported to associate with geographic origin by Pereira-Lorenzo et al [ 22 ] and with both parentage and pedigree in a study by Patzak et al [ 23 ]; in the former, the geographic origins in question related to a set of cultivars originating within Spain and the Canary Isles and in the latter, again, cultivars were clustered with only one of the two parental cultivars. In more recent studies using STRUCTURE analysis, Liang et al, [ 24 ] found two major groups, each with two subgroups, within a set of diploid Italian germplasm and international reference cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Oraguzie et al [ 18 ] reported that clustering did not reflect the pedigree or provenance within the genotypes. No clear patterns of clustering were identified in studies by Gaurino et al [ 20 ] or Garkava-Gustavsson et al [ 21 ] whilst clustering was reported to associate with geographic origin by Pereira-Lorenzo et al [ 22 ] and with both parentage and pedigree in a study by Patzak et al [ 23 ]; in the former, the geographic origins in question related to a set of cultivars originating within Spain and the Canary Isles and in the latter, again, cultivars were clustered with only one of the two parental cultivars. In more recent studies using STRUCTURE analysis, Liang et al, [ 24 ] found two major groups, each with two subgroups, within a set of diploid Italian germplasm and international reference cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellites, or SSRs, are the DNA markers of choice to uncover the genetic diversity between and within fruit species (Gupta et al, 1996), due to their high polymorphism level, abundance and co-dominant inheritance and reproducibility, as well as relative easiness of analysis (Madesis et al, 2013). Previously, many authors used this technique to determine the genetic diversity in order to identify duplicates and genetic relationships within and between Malus × domestica accessions (Garkava-Gustavsson et al, 2013;Gaši et al, 2010;Lassois et al, 2015;Liang et al, 2015;Oraguzie et al, 2005;Patzak et al, 2012;Pina et al, 2014;Urrestarazu et al, 2012). Nevertheless, only a few reports have demonstrated basic and detailed data on adaptability and fruit quality traits of Malus × domestica cultivars from different geographical areas, especially from species grown under the Greek climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, microsatellites or SSRs are the preferred DNA markers technique for the study of genetic relationship among species and the assessment of genetic diversity within crop species (Gupta et al, 1996), due to their high polymorphism level, abundance, codominant inheritance (Fernández et al, 2009), reproducibility and relative ease of analysis (Schlötterer, 2004). Many authors have used this technique to determine the genetic identities and the genetic diversity, and to identify duplicates and genetic relationships among Malus x domestica accessions (Guilford et al, 1997;Oraguzie et al, 2005;Gasi et al, 2010;Patzak et al, 2012) and Malus spp. (Hokanson et al, 1998(Hokanson et al, , 2001Guarino et al, 2006) around the world.…”
Section: Introductionmentioning
confidence: 99%